Models, Methods, and Morality Assessing Modern Approaches to the Greco-Roman Economy - Murray, Sarah C.; Bernard, Seth (Palgrave Studies in Ancient Economies, 2024)
XXII, 488 p. 24 illus., 8 illus. in color.